Natural Resources Management and Biological Sciences - Rhodes, Edward R.; Naser, Humood (IntechOpen, 2021)
The natural resources of the Earth are indispensable for the survival of humans, plants, and animals and for the state of biodiversity. The way they are managed determines the extent to which they will be preserved for future generations. Climate change underscores the need for the proper use of natural resources. This book brings together reviews of literature and the results of research studies on the status and management of soil, water, plant, and wildlife resources, especially as they relate to the biological sciences, in Africa, Asia, Europe, North America, and Latin America. It covers work on classification and inventories, impacts of anthropogenic activities, and exploitation and conservation. The book will be of interest to scientists and practitioners of natural resource management worldwide.